2005
DOI: 10.1007/11564126_45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Correlation Between Objective Rule Interestingness Measures and Real Human Interest

Abstract: Abstract. In the last few years, the data mining community has proposed a number of objective rule interestingness measures to select the most interesting rules, out of a large set of discovered rules. However, it should be recalled that objective measures are just an estimate of the true degree of interestingness of a rule to the user, the so-called real human interest. The latter is inherently subjective. Hence, it is not clear how effective, in practice, objective measures are. More precisely, the central q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 7 publications
0
37
0
1
Order By: Relevance
“…In Carvalho et al (2005) and Ohsaki et al (2004) various interestingness measures have been compared with real human interest, and the authors found that in many cases high ranking rules were considered uninteresting by the user. For example in Carvalho et al (2005) there was a positive correlation between an interestingness measure and real human interest only in 35.2% of studied cases.…”
Section: Mining Non-redundant Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Carvalho et al (2005) and Ohsaki et al (2004) various interestingness measures have been compared with real human interest, and the authors found that in many cases high ranking rules were considered uninteresting by the user. For example in Carvalho et al (2005) there was a positive correlation between an interestingness measure and real human interest only in 35.2% of studied cases.…”
Section: Mining Non-redundant Rulesmentioning
confidence: 99%
“…For example in Carvalho et al (2005) there was a positive correlation between an interestingness measure and real human interest only in 35.2% of studied cases. Also, for some datasets almost all measures gave good results and for others almost none.…”
Section: Mining Non-redundant Rulesmentioning
confidence: 99%
“…These measures are usually conflicting, i.e. an accurate rule is not necessarily interesting or easy to read, thus the searching process has to be multicriterial and dozens of such measures have been proposed and investigated [3,13].…”
Section: If "Some Conditions On the Values Of Predicting Attributes Amentioning
confidence: 99%
“…There are more than 40 objective measures for evaluating the interestingness of a rule [13], so choosing appropriate measures for the actual data characteristics is not a trivial task, as Carvalho et al clearly illustrated in their paper, too [3]. They analyzed the correlation between objective interestingness measures and the real human interest evaluated by experts from each domain, and proposed a ranking of objective quality measures.…”
Section: Interestingness Measuresmentioning
confidence: 99%
“…But, in the literature, they seek to find a correlation between real human interest and objective interestingness measures [5,[37][38][39]. BM_IRIL also proposes a new feature weighting technique that takes benefit maximization issues into account.…”
Section: Introductionmentioning
confidence: 99%